'Thank You for Taking the Time to Understand': A Critical Reflection on Peer-led Interventions in Early Experiences of Higher Education. Issue 3 (3rd July 2017) - Morton, Nick; Vincent, Wil; Schiessel Harvey, Nicki; Curzon, Rachel
ABSTRACT: Supporting students through their transition into Higher Education is a vital function of any successful university business. An interconnected series of interventions have been tested at Birmingham City University, UK, as part of a national project, based on peer-led models of student support piloted in the Built Environment school. We reflect in particular upon our pre-arrival mentoring program, our work to reach out to disengaged students, and our broader efforts to build connected student communities, and show that challenges in both academic and social spheres can be tackled through well designed interventions. In part this work has been enabled through a new staff post, that of Graduate Student Success Advisors. Survey work with the pilot cohort has indicated steadily rising and above sector average levels of engagement and self-confidence, and the interventions described are now part of an embedded approach to supporting students through the early stages of their studies, across all subject areas in our department.